A New Surface Charge Neutralizing Nano-Adjuvant to Potentiate Polymyxins in Killing Mcr-1 Mediated Drug-Resistant Escherichia coli - Hyejin Cho; Atanu Naskar; Sohee Lee; Semi Kim; Kwang-Sun Kim (MDPI AG, 2021)
Resistance to polymyxins when treating multidrug-resistant (MDR) Gram-negative bacterial infections limit therapeutic options. Here, we report the synthesis of a nickel (Ni) doped Zinc oxide (NZO) combined with black phosphorus (BP) (NZB) nanocomposite and its synergistic action with polymyxin B (PolB) against polymyxin-resistant Escherichia coli harboring mobilized colistin resistance (mcr-1) gene. NZB and PolB combination therapy expressed a specific and strong synergy against Mcr-1 expressing E. coli cells. The underlying mechanism of the synergy is the charge neutralization of the E. coli cell surface by NZB, resulting in a more feasible incorporation of PolB to E. coli. The synergistic concentration of NZB with PolB was proved biocompatible. Thus, the NZB is the first biocompatible nano-adjuvant to polymyxins against polymyxin-resistant E. coli cells, recognizing the physical status of bacteria instead of known adjuvants targeting cellular gene products. Therefore, NZB has the potential to revive polymyxins as leading last-resort antibiotics to combat polymyxin-resistant Gram-negative bacterial infections.